Knowledge and practices regarding menstruation among school going adolescents of rural Nepal - Sapkota, D; Sharma, D; Pokharel, H P; Budhathoki, Shyam Sundar; Khanal, Vijay Kumar (Journal of Kathmandu Medical College, 2014)
Background: Adolescence is a transition period from childhood to adult life during which pubertal development and sexual maturation take place, thus making physiological development a challenge adolescents have to face. There is a substantial lacuna in the knowledge towards menstruation among adolescent girls. Menstrual hygiene and management is an issue that is insufficiently acknowledged and has not received adequate attention. Objective: This study was done to assess the knowledge and practices regarding menstruation among school going adolescents. Methods: A descriptive study was done among sixty-one female adolescents of Shree Himali Secondary School, Panchkanya, Sunsari, where data were collected from the adolescents meeting the inclusion criteria. Results: It was found that 36.1% correctly reported about menstruation where most common informant was mother (39.3%). Dysmenorrhoea was the commonest problem faced during menstruation (78.7%) followed by back pain and excessive blood loss. More than half of respondents (54.1%) used sanitary pads and frequency of changing pads twice a day was highest (50.8%). Initial reaction was of fear/apprehension at menarche by 36.1% of girls whereas 44.3% perceived it as an expectant process. Girls still faced different types of restrictions like not being allowed to visit holy places, not being allowed to cook and touch male family member etc. Conclusion: Traditional beliefs regarding menstruation still persist and menstrual hygiene among the adolescents was found to be unsatisfactory. It highlights the need of targeted interventions to raise awareness and provision of family health education package to all girls. Menstrual hygiene is an issue that needs to be addressed at all levels. Journal of Kathmandu Medical College Vol. 2, No. 3, Issue 5, Jul.-Sep., 2013 Page: 117-121 DOI: http://dx.doi.org/10.3126/jkmc.v2i3.9962 Uploaded date : 3/4/2014